Mathematical Models of Differential Transformer Sensors Tuned to the Excitation Winding Resonance - Fayzullayevich, Amirov Sultov; Azamatovich, Sharapov Shuxrat (International Journal on Human-Computing Studies, 2023)
The analysis of the developed mathematical models of the new differential transformer sensors whose excitation circuit is adjusted to the resonance of voltages or currents showed that the sensitivity of the new sensors adjusted to the resonance of the excitation circuit is higher than the sensitivity of the sensors adjusted to the current resonance, and the original value of the excitation circuit is higher than the sensitivity of the sensors adjusted to the resonance of the currents. This showed that the sensitivity of the sensors is as many times higher than the sensitivity of the sensors tuned to voltage resonance. It was found that the change in the value and character of the load resistance in two identical new differential transformer sensors whose excitation circuit is tuned to voltage and current resonance, respectively, leads to a greater change in the current value in the excitation winding of the DTS tuned to voltage resonance.